Examination of Physicians’ Perception of the Indications of Colorectal Stents in the Management of Malignant Large Bowel Obstruction: A Provincial Survey - Jean-Frédéric LeBlanc; Myriam Martel; Alan N. Barkun (Canadian Journal of Gastroenterology and Hepatology)
Introduction. Data are conflicting when assessing indications for colorectal self-expandable metallic stents (SEMS) in managing acute malignant large bowel obstruction (MLO). In November 2014, European and American Societies published guidelines to aid in understanding which patients might benefit from colorectal stenting. Yet, there remain marked disparities in clinical practice. Methods. A web-based survey was sent to Gastroenterologists and Surgical Specialists across Quebec to assess physicians’ knowledge and adherence to the indications for colonic SEMS placement in the management of MLO using eight clinical scenarios. Results. Out of 112 respondents, 74% preferred surgical intervention in young, healthy individuals with MLO. Advanced age and comorbidities motivated 56.3% (95% CI 47.1–65.5%) of participants to opt for SEMS placement. In palliative settings of patients undergoing chemotherapy including bevacizumab, a minority of respondents followed guidelines, 12.5% (95% CI 6.4–18.6%) for young patients and 25.0% for elderly patients (95% CI 17.0–33.0%). The pooled overall adherence to guidelines was 50.4% (95% CI 40.7–59.3%). Conclusion. This survey suggests that guidelines recommendations are not being implemented by at least half of specialists involved in the care of patients with MLO. Future studies should attempt to identify possible barriers responsible for this impaired knowledge translation and tailored educational initiatives planned accordingly.